Synthesis and In Vitro AMPK Activation of Cycloalkyl/Alkarylbiguanides with Robust In Vivo Antihyperglycemic Action - Erika Gutierrez-Lara; Carlos Martínez-Conde; Edgar Rosales-Ortega; Juan José Ramírez-Espinosa; Julio C. Rivera-Leyva; David Centurión; Karla Carvajal; Daniel Ortega-Cuellar; Samuel Estrada-Soto; Gabriel Navarrete-Vázquez (Journal of Chemistry)
This work describes the design, synthesis in one step, and the in vitro, in vivo, and in silico antidiabetic evaluation of a series of ten alicyclic and aromatic (alkyl +aryl: alkaryl)biguanides, analogues of metformin and phenformin. The design was conceived using isosteric replacement, chain-ring transformation, and lower and higher homologation strategies. All compounds were obtained as crystals and their structure was confirmed on the basis of their spectral data (NMR and mass spectra), and their purity was ascertained by microanalysis. Compounds were in vitro evaluated as activators of AMP-Activated Protein Kinase (AMPK). The results indicated that compounds 4, 5, and 6 showed similar or even better effect compared to metformin. Docking analysis was performed with regulatory subunit γ of AMPK, showing several interactions with nucleotide binding pocket. The in vivo evaluation of compounds 4–6 at a single dose of 50 mg/kg was performed in a murine experimental model of diabetes. The results showed an important and robust decrease of plasmatic glucose levels (−40%). Compound 6 was selected for an oral glucose tolerance test, showing an antihyperglycemic effect similar to metformin. The in vivo results indicated that compounds 4–6 may be effective in treating experimental T2DM.